LAND COVER/USE IN THE CANTONS OF UPALA, GUATUSO AND LOS CHILES IN THE YEAR 2011 - Barrantes-Sotela, Omar; Sandoval-Murillo, Luis (Revista Geográfica de América Central., 2016)
The use of land is essential to identify different agro-economic activities and natural resources present in a specific area. However, the lack of updated spatial information –for more than thirty-five years, regarding the uses and coverages of land in Upala, Guatuso and Los Chiles, Alajuela, Costa Rica has limited the decision-making process concerning land planning, which aims at supporting a balanced development between different entities in the territory. Using remote sensing methods major land uses and land covers were identified in 2011 for these cantons. This information serves as a critical tool to generate other inputs required in the preparation of technical proposals on planning and land use planning.